Protein and Anthocyanin Production of Waterleaf Shoots (Talinum triangulare (Jacq.) Willd) at Different Levels of Nitrogen+Potassium and Harvest Intervals - Hilda Susanti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
The experiment was conducted at IPB Experimental Station, Leuwikopo, Dramaga, Bogor, from November 2009 untilFebruary 2010 to study the effect of different nitrogen+potassium rates and harvest intervals on protein and anthocyaninproduction of waterleaf shoot (Talinum triangulare (Jacq.) Willd). A randomized complete block design was used with threereplications of two factors, which were four N+K dosages (50 kg urea + 50 kg ha-1 KCl, 50 kg urea + 100 kg ha-1 KCl, 100 kgurea + 50 kg ha-1 KCl, 100 kg urea + 100 kg ha-1 KCl) and three harvest intervals (30, 15, and 10 days). The results showedthat interaction of 100 kg urea + 100 kg ha-1 KCl and 15-day harvest interval produced the highest content (8.29 mg g-1 freshweight) and production (4.72 g plant-1) of protein. The interaction of N+K dosages and harvest intervals were not signifi cantin affecting the anthocyanin content. The highest production of anthocyanin was produced by single treatment of 100 kg urea+ 100 kg ha-1 KCl (152.23 μmol plant-1) and 10 days harvest interval (165.47 μmol plant-1), respectively. Leaf protein levelsnegatively correlated with anthocyanin content.Keywords: anthocyanin, fertilizer, harvest interval, protein, Talinum triangulare